Inoculation with Azospirillum brasilense associated with silicon applied to correct soil acidity and nitrogen rates in corn and wheat crops - Galindo, Fernando Shintate (2020)
Alternative management practices are needed to minimize the need for chemical fertilizer use in non-leguminous cropping systems. The use of biological agents which can fix atmospheric nitrogen and promote plant growth has shown potential as an option to improve soil nutrient availability to grass crops. In recent years, studies investigating the effects of silicon (Si) have increased substantially, especially in grain crops. This increased interest in Si is likely due to the beneficial effects of Si application on plant resistance to abiotic and biotic stresses, reflecting on greater plant development. This research was developed to investigate if inoculation of corn and wheat with Azospirillum brasilense associated with Si can enhance nitrogen use efficiency (NUE) and improve plant nutrition and yield, leading to a greater economic profit. The study was set up in a Rhodic Haplustox under no-till system, located in Selvíria, state of Mato Grosso do Sul, Brazil. The field trial took place during the 2015/16 (November-March), 2016 (April-September), 2016/17 (November-March) and 2017 April-September) seasons, with corn and wheat crops in sucession (spring/summer and winter seasons for corn and wheat, respectively). Treatments were tested in a randomized completely block design with four replicates, arranged in a full factorial design 5 × 2 × 2 and included: i) five N application rates, as urea source, applied in side-dressing (0, 50, 100, 150 and 200 kg ha-1); ii) two liming sources (Ca and Mg silicate as Si source and dolomitic limestone); and iii) and two seed inoculation (with and without A. brasilense). Increasing N rates positively influenced corn and wheat nutrition with increased nutrient and Si uptake in shoot, straw and grain, plant development and grain filling, leading to a greater grain yield. The average nutrient uptake in corn straw and grain in descending order was K > N > Ca > Si > Mg > S > P > Fe > Mn > Zn > Cu > B for straw; and N > K > P > S > Mg > Ca > Si > Fe > Zn > Mn > B > Cu for grains. For wheat, the average nutrient uptake was K > N > Si > Ca > S > Mg > P > Fe > Mn > Zn > B > Cu in straw; and N > K > P > S > Mg > Si > Ca > Fe > Mn > Cu > Zn > B in grains. The application of Ca and Mg silicate as a Si source had small effects on corn and wheat development and grain yield. Although silicate application as Si source did not greatly favor NUE, Si also did not negatively affect the inoculation and N fertilization, and correlates positively with nutritional, productive components, soil chemical attributes and corn and wheat grain yield. After four cropping seasons (2015/16, 2016, 2016/17 and 2017, with corn and wheat in succession), silicate application was more efficient as a liming source to reduce soil acidity, with decreased soil H+Al and Al content, and increased pH and base saturation (V). Inoculation with A. brasilense increased NUE in corn crop by 19.1% and wheat by 38.6% (average of both years, in both crops) leading to a greater leaf chlorophyll index (LCI), nutrient uptake, corn development, grain filling, grain yield and operating profit. Also, inoculation could increase corn and wheat leaf N concentration when associated with silicate application. Inoculation provided greater corn grain yield by 5.6% (average of both years). Under high N application rates (200 kg N ha-1), inoculation provided an increase of 11.4% on corn grain yield, in 2015/16. In the absence of N fertilization, inoculation provided an increase of 20.2% in grain yield, in 2016/17. In wheat crop, with application of 200 kg N ha-1, inoculation provided an increase of 22.2% in shoot N uptake, in 2016. Inoculation provided greater wheat grain yield by 6.8% (average of both years). The application of 200 and 140 kg N ha-1 in side-dressing with dolomitic limestone, associated with A. brasilense inoculation provided greater corn grain and wheat yield, respectively. However, the highest economic return was obtained with 100 kg N ha-1, with limestone and inoculation, ensuring profitability from production of irrigated corn and wheat under tropical condition (Brazilian Savannah - Cerrado).